Daily Intake of a Phaseolus vulgaris L. Snack Bar Attenuates Hypertriglyceridemia and Improves Lipid Metabolism-Associated Plasma Proteins in Mexican Women: A Randomized Clinical Trial - Ramírez-Jiménez, Aurea K.; Luzardo-Ocampo, Ivan; Cuellar-Nuñez, M. Liceth; Anaya-Loyola, Miriam Aracely; León-Galván, Ma. Fabiola; Loarca-Piña, Guadalupe (Frontiers in Nutrition, 2022)
Current efforts to prevent dyslipidemia are focused on the development of functional products as an alternative for hypertriglyceridemia management. This study assessed the metabolic effect of the daily consumption of a bean and oats snack bar (BOSB) on hypertriglyceridemia biomarkers among Mexican women. An 8-weeks randomized parallel clinical trial (ID: NCT0496694, https://clinicaltrials.gov/ct2/show/NCT04966494) was conducted with 26 hypertriglyceridemic women allocated to BOSB group (TG = 208.18 ± 56.97 mg/dL) and control group (TG = 182.28 ± 51.39 mg/dL). Only the BOSB group consumed 50 g of the product per day. Fasting blood samples were taken from women with an adherence ≥ 90%. A targeted proteomic analysis with plasma samples of control and BOSB groups were conducted using a human obesity antibody array kit and bioinformatic tools provided by the Ingenuity Pathways Analysis (IPA) software. Serum TG levels in the BOSB group decreased by 37.80% (132.04 ± 27.83 mg/dL) compared with the control group (178.87 ± 32.01 mg/dL); glucose levels decreased by 5.69% in the BOSB group (87.55 ± 3.36 mg/dL). A modest body weight (5%) reduction was also found. Forty proteins were differentially modulated by the BOSB consumption (fold change > 1.2). The proteomic analysis revealed the involvement of BOSB bioactives in prevention of monocytes recruitment and localized inflammatory response, inhibition of pre-adipocyte maturation and adipogenesis, inhibition of hepatic b-oxidation, and potential satiety regulation. These results are promising since the mere intervention with the BOSB reduced serum TG without diet restriction, giving insights for further research in prevention of hypertriglyceridemia.